Organizational justice and employee performance: Mediating organizational commitment - Tajudin Tajudin; Wahid Sumarjo; Haerofiatna Haerofiatna; Wahyudi Wahyudi (Institute of Computer Science (IOCS), 2025)
This study aims to analyze the influence of organizational justice on employee performance with organizational commitment as a mediating variable in PT Sokonindo Automobile. The research method uses a quantitative approach with Partial Least Squares-Structural Equation Modeling (PLS-SEM) analysis. The research sample amounted to 179 respondents which were determined through simple random sampling techniques. The results of the study show that organizational justice has a positive and significant effect on employee performance, and has a strong influence on increasing organizational commitment. In addition, organizational commitment has been proven to make a significant contribution in driving performance improvement. Mediation analysis shows that organizational commitment mediates positively and significantly the relationship between organizational justice and employee performance. The values of R² and Q² confirm that the model has good predictive power and adequate predictive relevance. These findings underscore that justice in distribution, procedures, and interactions is an important foundation in building employee psychological attachment that ultimately improves work performance. This research provides implications for the development of equity-based HR policies and offers a theoretical perspective on the psychological mechanisms that link justice and performance through organizational commitment